Mucinous and Signet Ring Cell Differentiation Affect Patterns of Metastasis in Colorectal Carcinoma and Influence Survival. (April 2017) - Kermanshahi, Taher Reza; Magge, Deepa; Choudry, Haroon; Ramalingam, Leksmi; Zhu, Benjamin; Pingpank, James; Ahrendt, Steven; Holtzman, Matthew; Zeh, Herbert; Bartlett, David; Zureikat, Amer; Pai, Reetesh K.
Peritoneal metastasis in colorectal carcinoma is associated with a dismal prognosis; however, features that correlate with patterns of metastatic spread are not well characterized. We analyzed the clinicopathologic and molecular features of 166 patients with colorectal carcinomas stratified by metastases to the peritoneum or liver. Mucinous and signet ring cell differentiation were more frequently observed in colorectal carcinoma with peritoneal dissemination compared to colorectal carcinoma with liver metastasis (mucinous differentiation: 62% vs 23%, P < .001; signet ring cell differentiation: 21% vs 0%, P < .0001). The significant association of mucinous differentiation with peritoneal dissemination compared with liver metastasis was identified in patients with both synchronous and metachronous development of metastasis ( P < .01). In contrast, colorectal carcinomas with liver metastasis were more frequently low-grade (90% vs 72%, P = .005) and associated with dirty necrosis (81% vs 56%, P = .001) compared with colorectal carcinomas with peritoneal dissemination. No significant differences were identified between colorectal carcinoma with peritoneal metastasis versus liver metastasis with respect to KRAS mutations, BRAF mutation, or high levels of microsatellite instability. Patients with tumors involving the peritoneum had a significantly worse overall survival in comparison to patients with liver metastasis lacking peritoneal involvement ( P = .02). When including only those patients with peritoneal metastasis, the presence of any mucinous or signet ring cell differentiation was associated with a significantly worse overall survival ( P = .006). Our findings indicate that mucinous and signet ring cell differentiation may be histologic features that are associated with an increased risk of peritoneal dissemination and poor overall survival in patients with peritoneal metastasis.